Implementation of digital health in rural populations with chronic musculoskeletal conditions: A scoping review protocol. - Lara Campos; Daniela Costa; Helena Donato; Baltazar Nunes; Eduardo B Cruz (PLoS ONE)
Musculoskeletal conditions are a major source of disability worldwide, and its burden have been rising in the last decades. Rural areas, in particular, are associated with higher prevalence of these conditions as well as higher levels of disability, which is likely related to other determinants that affect these communities. Although digital health has been identified as a potential solution to mitigate the impact of these determinants, it is also known that these populations may face barriers that limit the implementation of these interventions. Therefore, the aim of this scoping review is to comprehensively map the evidence regarding the implementation of digital health interventions in rural populations with chronic musculoskeletal conditions. We will include studies published from the year 2000; that report the use of digital interventions that promote prevention, treatment or monitoring of any chronic musculoskeletal condition or chronic pain from musculoskeletal origin, in patients that live in rural areas. This protocol follows the methodological framework for scoping reviews proposed by Arksey and O'Malley, as well as the Joana Briggs Institute (JBI) approach. We will conduct the search on Medline (PubMed), EMBASE, Web of Science and Scopus, as well as grey literature databases. Two independent reviewers will screen titles and abstracts followed by a full-text review to assess the eligibility of the articles. Data extracted will include the identification of the digital interventions used, barriers and enablers identified by the patients or healthcare providers, the patient-level outcomes measured, and the implementation strategies and outcomes reported. By mapping the evidence on the implementation of digital health interventions in rural communities with musculoskeletal conditions, this scoping review will enhance our understanding of their applicability in real-world settings.